Alcohol Use and the Risk of Colorectal Liver Metastasis: A Systematic Mapping Review - Roshan Sapkota; Joseph Zakaria; Emily Glenn; Heather Richard; Ahmad Rimawi; Martin Tobi; Benita McVicker (Biology, 2023)
The consumption of alcohol has long been associated with the development of liver disease as well as cancers including colorectal cancer (CRC). Leading healthcare concerns include the prevalent use of alcohol and the high burden of CRC mortality. Many CRC deaths are attributed to the development of colorectal liver metastasis (CRLM) as the liver is the foremost site of CRC spread. However, an association has not been defined for the role of alcohol intake and related liver injury with the development of CRLM. Here, a mapping review of recent research was undertaken to evaluate the relationship between alcohol consumption and the risk of CRLM. The literature search revealed 14 articles meeting the inclusion criteria that included patient database analyses and preclinical studies. Most of the human data analyses found alcohol use independently associates with worse CRC outcomes. The preclinical evaluations identified several pathways involved in the alcohol-mediated promotion of CRLM burden and CRC cell metastatic behavior. The limited number of studies identified exposes a significant need for more prospective analyses to define the role of alcohol intake and advanced CRC as well as the translation of preclinical research to fully characterize targetable mechanisms for the generation of new therapeutic options.